Comparing The Effectiveness of Mind Mapping and Summarizing in Enhancing Student Learning Outcomes in Flipped Classroom Model - Munawwarah Munawwarah; Vika Puji Cahyani (Jurnal Studi Guru dan Pembelajaran)
The urgency of this research lies in the need to explore and compare the effectiveness of two distinct teaching strategies, mind mapping and summarizing, within the flipped classroom model, considering the challenges in determining the most effective method to enhance student learning outcomes across various disciplines, as well as understanding factors that may influence learning success, such as student engagement and material quality. This study examines the effectiveness of the flipped classroom model in enhancing students' learning outcomes, focusing on two distinct instructional strategies: mind mapping and summarizing. Using a posttest-only control group design, the research compared two groups: Class A (mind mapping) and Class B (summarizing), each consisting of 20 fifth-semester chemistry education students. Students engaged with materials independently before class and presented their understanding using their respective methods. Data analysis included descriptive statistics, the Shapiro-Wilk test for normality, Levene's test for homogeneity of variances, and the Mann-Whitney U test for comparing post-test scores. The results showed that Class A followed a normal distribution (p > 0.05), whereas Class B did not meet the normality assumption (p < 0.05). However, the Levene's test indicated homogeneity of variances between the groups (p > 0.05). The Mann-Whitney U test revealed no statistically significant difference in post-test scores (U = 156.5, p = 0.244), with mean scores of 86.83 for Class A and 86.42 for Class B. Effect size analysis using Cohen's d demonstrated a negligible effect (d = 0.06), suggesting equivalent effectiveness between the two methods. These findings highlight that both mind mapping and summarizing are equally effective within the flipped classroom model, reinforcing its versatility in diverse learning contexts. Future research is recommended to explore additional factors, such as student engagement and material quality, that may influence learning outcomes in this instructional model.